2017
DOI: 10.1080/10408398.2016.1277971
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer properties and mechanisms of action of thymoquinone, the major active ingredient ofNigella sativa

Abstract: Over the past two decades, studies have documented the wide-range anti-cancer effects of Nigella sativa, known as black seed or black cumin. Thymoquinone (TQ), its major active ingredient, has also been extensively studied and reported to possess potent anti-cancer properties. Herein, we provide a comprehensive review of the findings related to the anti-cancer activity of TQ. The review focuses on analyzing experimental studies performed using different in vitro and in vivo models to identify the anti-prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 130 publications
(163 reference statements)
3
67
0
4
Order By: Relevance
“…[54] Especially in cancer cells, TQ also showed a hindering effect on proliferation due to over-phosphorylation of some protein kinases such as AKT, ERK, and JNK. [55,56] Herein, we observed that an increase in the phosphorylation of all studied kinases (GSK-3, ERK1/2, and JNK-2) and factors (CREB) except activation of AKT suggesting the activation of a cell survival cascade parallel to the increase in the surviving neurons in hippocampal regions by TQ administration. GSK-3 may be a sensor determining the neuronal cell fate in the brain and GSK-3β, which is active in resting cells, is inactivated by phosphorylation.…”
Section: Discussionmentioning
confidence: 64%
“…[54] Especially in cancer cells, TQ also showed a hindering effect on proliferation due to over-phosphorylation of some protein kinases such as AKT, ERK, and JNK. [55,56] Herein, we observed that an increase in the phosphorylation of all studied kinases (GSK-3, ERK1/2, and JNK-2) and factors (CREB) except activation of AKT suggesting the activation of a cell survival cascade parallel to the increase in the surviving neurons in hippocampal regions by TQ administration. GSK-3 may be a sensor determining the neuronal cell fate in the brain and GSK-3β, which is active in resting cells, is inactivated by phosphorylation.…”
Section: Discussionmentioning
confidence: 64%
“…Reportedly, TQ interferes in the phosphorylation and subsequent activation of several upstream tyrosine kinases (e.g., MAPK, Akt, mTOR, PIP3) that are involved in tumor cell proliferation signaling pathways (Yi et al, 2008; Kundu et al, 2014b). Transcriptional factors (e.g., Nrf2, NF-κB, and STAT-3), key players in various oncogenesis process, are other crucial molecular targets of TQ (Kundu et al, 2014b; Darakhshan et al, 2015; Majdalawieh et al, 2017). By regulating the activation of these transcription factors, TQ can counteract different tumorigenic processes including inflammation, cell proliferation, cell survival, angiogenesis, cell invasions, and metastasis.…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…of TQ have been identified that are somehow involved in tumorigenesis or development of drug resistance (Kundu et al, 2014b) (Figure 1). Though treatment with TQ alone has shown antitumor efficacy in several in vitro and in vivo studies as mentioned in details in a recent review (Majdalawieh et al, 2017), the lower efficacy (Effenberger et al, 2010) and poor bioavailability (Ganea et al, 2010; Elmowafy et al, 2016) of TQ is the primary bottleneck for considering it as the primary therapeutic agent. Therefore, in this review, we proposed the potential role of TQ as an adjuvant therapy with different types of conventional cancer treatments namely surgery, radiotherapy, chemotherapy, and immunotherapy either to prevent carcinogenesis or to potentiate the efficiency of conventional therapeutic modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, N. sativa also contains It is evident from the previous multiple studies that N. sativa showed cytotoxic effects in different types of cancer including lung cancer, breast cancer, cervical cancer, ovarian cancer and colorectal cancer (Majdalawieh and Fayyad, 2016). N. sativa showed cytotoxic, anti -proliferative, pro-apoptotic, anti-oxidant, anti-metastatic, and NK-dependent cytotoxic effects due to its main constituent thymoquinone (Majdalawieh et al, 2017). As N. sativa have promising results for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%